2023
DOI: 10.3390/nu15133010
|View full text |Cite
|
Sign up to set email alerts
|

Central Regulation of Eating Behaviors in Humans: Evidence from Functional Neuroimaging Studies

Abstract: Neuroimaging has great potential to provide insight into the neural response to food stimuli. Remarkable advances have been made in understanding the neural activity underlying food perception, not only in normal eating but also in obesity, eating disorders, and disorders of gut–brain interaction in recent decades. In addition to the abnormal brain function in patients with eating disorders compared to healthy controls, new therapies, such as neurofeedback and neurostimulation techniques, have been developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…Thus, enhanced function in the MFG may help individuals resist the temptation of hedonic foods following exercise. Previous studies have also suggested that the MFG is involved in eating regulation [ 63 , 64 ]. Second, the present study has also found the rsFC of PCB–MOG totally mediated this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, enhanced function in the MFG may help individuals resist the temptation of hedonic foods following exercise. Previous studies have also suggested that the MFG is involved in eating regulation [ 63 , 64 ]. Second, the present study has also found the rsFC of PCB–MOG totally mediated this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…By aligning these observations across species, we provide a comprehensive view of the psychological and neurological dynamics that govern eating behavior. This alignment is particularly critical given the constant exposure to food-related stimuli in modern obesogenic environments, underscoring the need for a phase-specific understanding of eating behavior ( 22 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a study on coordinated looking and reaching in non-human primates showed beta frequency to positively correlate with neural mechanisms responsible for inhibiting natural behavior such as coordinated movement (Hagan and Pesaran, 2022). Regarding the connection with BED and disordered eating, the modulation of GABA action has been mentioned as a potential target for future studies (Mele et al, 2020), but overall, research on the neural response to food stimuli is rare (Chae and Lee, 2023).…”
Section: Discussionmentioning
confidence: 99%